Uroom: connecting teachers and students for class assignment - Lim, Jing Xiang (2022)

(untitled)
In this report, a web application will be developed to help the teachers and students to do the assignment and form and manage the assignment group in a more convenient way. Moreover, some problems like free rider problem that the teachers and students may meet during doing the assignment will be one of the main focuses in this project. Some solutions will be proposed to reduce the likelihood of free rider problem occurring. This application will have six modules which are Assignment Room module, Assignment module, Assignment Group module, Chatroom module, Real Time Collaborative module, and Assignment Submission module. The Assignment Room module will enable the teachers to create a room and invite students to the room. The Assignment module will enable the teachers to upload assignment and create the task templates. The Assignment Group module will enable the teachers to manage the students’ assignment group and use the auto assign assignment group function to assign assignment group for students automatically. Meanwhile, the students can form the assignment group manually by sending a group forming request and manage the assignment group. A task management function will be integrated into this Assignment Group module. Students can manage the tasks that they have done. Every task will have a task history. This task history can be used to track the students’ work. The Chatroom module will enable the students to discuss assignment. Hence, they no need to create a group chat in another application anymore. The Real Time Collaborative module will enable the students to do the assignment together in real time. The Assignment Submission Module will enable the students to submit assignment and write reviews to their groupmates while teachers can view the submission and upload the marks. Furthermore, this application will also store the ratings of the students. Hence, students can have something to refer before forming the assignment group. This project will use React.js for the frontend development and Node.js for the backend development.